Differences in Effective Ploidy Drive Genome-Wide Endosperm Expression Polarization and Seed Failure in Wild Tomato Hybrids. Issue 1 (22nd March 2019) - Roth, Morgane; Florez-Rueda, Ana M; Städler, Thomas
Abstract: Parental imbalances in the endosperm leading to impaired development and eventual hybrid seed failure are common causes of postzygotic isolation in flowering plants. Endosperm sensitivity to parental dosage is reflected by canonical phenotypes of "parental excess" in reciprocal interploid crosses. Moreover, parental-excess traits are also evident in many homoploid interspecific crosses, potentially reflecting among-lineage variation in "effective ploidy" driven by endosperm properties. However, the genetic basis of effective ploidy is unknown and genome-wide expression perturbations in parental-excess endosperms from homoploid crosses have yet to be reported. The tomato clade ( Solanum section Lycopersicon ), encompassing closely related diploids with partial-to-complete hybrid seed failure, provides outstanding opportunities to study these issues. Here, we compared replicated endosperm transcriptomes from six crosses within and among three wild tomato lineages. Strikingly, strongly inviable hybrid crosses displayed conspicuous, asymmetric expression perturbations that mirror previously characterized parental-excess phenotypes. Solanum peruvianum, the species inferred to have evolved higher effective ploidy than the other two, drove expression landscape polarization between maternal and paternal roles. This global expression divergence was mirrored in functionally important gene families such as MADS-box transcription factors and E3 ubiquitin ligases, and revealed differences in cell cycle tuning that match phenotypic differences in developing endosperm and mature seed size between reciprocal crosses. Our work starts to uncover the complex interactions between expression divergence, parental conflict, and hybrid seed failure that likely contributed to plant diversity.